E.S.R. studies of TCNQ complex salts - Owens, Glynnis Anne (1978)
The technique of electron spin resonance was used to study the magnetic properties of a number of complex salts of 7,7' ,8,8'-tetracyanoquinodimethane (TCNQ) in order to obtain a more complete understanding of the electronic states in these materials. All but one of the cations used in the preparation of these compounds were divalent and their TCNQ complex salts exhibit magnetic behaviour characteristic of thermally accessible triplet excitons. Three of these compounds, 1,2-di(N-p-cyanobenzyl-4-pyridinium)ethylene (DCBP)-(TCNQ)3' 1,2-di(N-methyl-4-pyridinium)ethane (DMPA)-(TCNQ)4 (I), and 1,4-di(N-pyridinium)butane (DPB)-(TCNQ)4' were available as single crystals and could be studied in detail. Four of these, however, were only available in polycrystalline form and these were DMPA(TCNQ)4(II) and 1,2-di(N-alkyl-4-pyridinium)ethylene (DRPE)-(TCNQ)S' in which R equals n-propyl (P), n-butyl (B), and cyclohexyl (H). The existence of two phases (I and II) of DMPA(TCNQ)4' first indicated by the electrical data, was supported by the different magnetic behaviour observed in this work. The absolute magnitudes of the signal intensity for DPPE(TCNQ)S' DHPE(TCNQ)S and DMPA(TCNQ)4 (II) ,were found to be well described by an approximate solution to the Heisenberg Hamiltonian, which indicates an exciton band is present in these compounds. The absence of dipolar splitting and the high d.c. conductivity supports this interpretation. However, DMPA(TCNQ)4(I), DPB(TCNQ)4' DBPE(TCNQ)S and DCBP(TCNQ)3 gave results indicative of localised triplet excitons. The latter compound exhibits dipolar splitting, and information concerning the exciton dynamics could be obtained. These results were consistent with the conductivity data and, where available, the crystal structure determinations. The complex salt TPT(TCNQ)4 was available in single crystal form and contained the only trivalent cation studied in this work. The temperature independent signal intensity indicated that triplet excitons were not present, and this behaviour was typical of Pauli paramagnetism. This observation was consistent with the semi-metallic d.c. conductivity observed and was explained in terms of the high degree of disorder present, as indicated by the crystal structure determination.